P125 Chondrocytes derived from mesenchymal stem cells differentiated in the presence of plasma-derived extracellular vesicles from osteoarthritic patients express disease-related genes. (21st February 2018) - Pieters, BCH; Waterborg, CEJ; Arntz, OJ; Blom, AB; van der Kraan, PM; van de Loo, FAJ
Abstract : Introduction: Osteoarthritis (OA) is an age-related musculoskeletal disease and the most common form of arthritis characterised by low grade synovial inflammation and articular cartilage degeneration. OA has many risk factors such as genetic predisposition, age and gender, but also joint specific (e.g. trauma) and systemic (obesity, hormones). Also many different cell types have been implicated in the pathogenesis of OA and interplay between these cells contribute to the dynamic events associated with disease. Recently, extracellular vesicles (EVs) have emerged as mediators of intercellular communication. There is however very little known about the pathophysiological role of EVs in musculoskeletal diseases. In this study, we investigate whether plasma EVs from OA patients can drive chondrocyte terminal differentiation, a pathophysiological process observed in affected joints and a hallmark of OA. Objectives: Study the effect of plasma-derived EVs from OA patients during chondrogenenic differentiation of mesenchymal stem cells. Methods: Plasma-derived extracellular vesicles (pEVs) were isolated from plasma of OA patients and age-matched healthy controls using size-exclusion chromatography. EV containing fractions were characterised according to ISEV guidelines. 1 Pelleted MSCs were stimulated with TGF-β and BMP-2 to induce chondrogenic differentiation, either in the presence of pEVs isolated from OA patients or healthy controls. After 8 days, RNA was isolated and RT-qPCR was performed to determine the gene expression profiles. Results: No significant difference was observed in particle concentration, size or protein concentration between OA patients and age-matched controls. In the presence of pEVs from OA patients MSC-derived chondrocytes showed a significant increase in the expression of MMP13 (6.1-fold), RUNX2 (1.9-fold) and RANKL (2.3-fold), compared to pEVs from healthy controls. A trend towards higher ADAMTS5 expression (2.5-fold, p = 0.0685 ) with OA pEVs was also observed. Additionally, we found significantly higher expression of WISP1 (24-fold), suggesting activation of Wnt signalling. All other proinflammatory genes tested were not significantly different between the two groups. Conclusions: Here, we show direct evidence that circulating pEVs from OA patients can enhance OA-related genes, like MMP13, in MSC-derived chondrocytes. The expression profile found suggest the presence of Wnt-proteins on pEVs from OA patients, which are known to be involved in cartilage development and can induce chondrocyte hypertrophy, and we previously have shown that WISP-1 expression is a feature of experimental and human OA. 2 We showed that pEVs can transfer disease-related phenotypic changes and this might implicate them in the pathophysiological process of OA. References: . Lötvall J, et al. Journal of Extracellular Vesicles 2014. . Blom AB, et al. Arthritis & Rheumatology 2009. Disclosure of interest: None declared